A specific role of village doctors in reducing disparities: a quantile regression analysis of end-of-life medical care - Yuan Fang; Shih-Ting Huang; Chengrui Xiao (BMC Palliative Care)
Abstract Background In developing countries, the delivery of medical care to rural residents has been experiencing long-standing challenges and disparities. Since the 1960s, China has established the village doctors’ system to provide preventive and primary care to improve rural residents’ health. Nevertheless, how village doctors affect the medical spending and the end-of-life (EOL) quality for older people in rural China has not received sufficient attention. Family care has long been the mainstream of old age care in rural China, the accessibility to appropriate medical care is hence crucial. Village doctors are the most accessible medical care providers for rural older people. As a result, this study aims to uncover the importance of village doctors in EOL medical care for rural older people in China. Methods The analysis is based on the Chinese Longitudinal Healthy Longevity Survey (CLHLS), which has national representativeness and contains information about the oldest old at an average age of 80 in China, with available information from 2002 to 2019. We adopt the quantile regression to illustrate the heterogeneous impacts of village doctors on the EOL medical care spending from the distribution perspective. We then employ the ordered logit model and ordinary least squares regression to estimate the effects of village doctors on rural older people’s EOL life quality measured by the status before dying and the number of bedridden days. Results We find that the EOL medical care spending is significantly increased by the presence of village doctors, especially high-quality ones. The disparities in the EOL medical care in rural and urban China are significantly reduced by high-quality village doctors. However, high-quality village doctors are still insufficient to meet the needs of rural older people regarding the high-end EOL medical care. The empirical results suggest that village doctors can significantly improve older people’s quality of life before death in rural China. Conclusion Our analysis highlights the importance of village doctors in providing EOL medical care to older people in rural China. It is crucial for governments to improve the village doctors’ system, so that older residents in rural China can obtain high-quality EOL medical care services in their own communities and have a better quality of life before death.